Environmental constraints guide migration of Malaria parasites during transmission - Hellmann, Janina K.; Münter, Sylvia; Kudryashev, Mikhail; Heiß, Kirsten; Müller, Ann-Kristin; Matuschewski, Kai; Spatz, Joachim P.; Schwarz, Ulrich S.; Frischknecht, Friedrich (PLoS pathogens, 2011)
Author Summary Guidance of motile cells plays an important role during the life of a multi-cellular organism from early embryogenesis to the intricate interactions of immune cells during an infection. These migrations, like those of pathogens, can be directed by both chemical and physical cues. The malaria parasite needs to migrate immediately after being injected into the skin of the host by a mosquito bite. The malaria parasite forms deposited in the skin are called sporozoites. These must penetrate the dermis of the host to reach and enter a blood vessel. It is not clear if the sporozoites follow chemical cues or rely on the physical context of the environment. We show here, using in vivo imaging that sporozoites migrate along different paths in different skin environments. Introducing a novel assay for the study of cell migration in general we show that these in vivo paths can be largely recreated in vitro by placing sporozoites in a micro-patterned environment. This shows that environmental constraints are sufficient to guide sporozoite migration in the skin dermis. We further speculate that sporozoites have evolved to migrate at the fastest speed possible for efficient dispersal and show that a parasite lacking a surface protein has substantial defects in tissue dispersal and thus cannot efficiently infect the host.